Photo, thermal and chemical degradation of riboflavin - Sheraz, Muhammad Ali; Kazi, Sadia Hafeez; Ahmed, Sofia; Anwar, Zubair; Ahmad, Iqbal (Beilstein Journal of Organic Chemistry, 2014)
Riboflavin (RF), also known as vitamin B2, belongs to the class of water-soluble vitamins and is widely present in a variety of food products. It is sensitive to light and high temperature, and therefore, needs a consideration of these factors for its stability in food products and pharmaceutical preparations. A number of other factors have also been identified that affect the stability of RF. These factors include radiation source, its intensity and wavelength, pH, presence of oxygen, buffer concentration and ionic strength, solvent polarity and viscosity, and use of stabilizers and complexing agents. A detailed review of the literature in this field has been made and all those factors that affect the photo, thermal and chemical degradation of RF have been discussed. RF undergoes degradation through several mechanisms and an understanding of the mode of photo- and thermal degradation of RF may help in the stabilization of the vitamin. A general scheme for the photodegradation of RF is presented.
Keywords: chemical degradation; degradation products; photodegradation; riboflavin; stability; thermal degradation

Monograph on Riboflavin (Her Majesty’s Stationary Office, 2013)

(untitled) - Vargas, F.; Rivas, C.; Machado, R. (J. Pharm. Sci., 1992)

(untitled) - Ahmad, I.; Hussain, W.; Fareedi, A. A. (J. Pharm. Biomed. Anal., 1992)

(untitled) - Navaratnam, S.; Land, E. J.; Parsons, B. J.; Ahmad, I.; Phillips, G. O. (Photochem. Photobiol., 1983)

(untitled) - Tønnesen, H. H. (Int. J. Pharm., 2001)

The Photostability of Drugs and Drug Formulations - Tønnesen, H. H. (CRC Press, 2004)

(untitled) - Tønnesen, H. H. (Photodecomposition of drugs. In Encyclopedia of Pharmaceutical Technology, 2007)

Pharmaceutical Stress Testing - Baertschi, S. W. (Taylor & Francis Group, 2005)

(untitled) - Bhalekar, M. R.; Harinarayana, D.; Madgulkar, A. R.; Pandya, S. J.; Jain, D. K. (Asian J. Chem., 2008)

Handbook of Vitamins - Rivlin, R. S. (Riboflavin (vitamin B2), 2007)

Vitamins in Foods Analysis; Bioavailability and Stability - Ball, G. F. M. (CRC Press, 2006)

The Vitamins Fundamental Aspects in Nutrition and Health - Combs, G. F., Jr (Academic Press, 2008)

Flavins Photochemistry and Photobiology - Edwards, A. M. (General properties of flavins, 2006)

(untitled) - Cairns, W. L.; Metzler, D. E. (J. Am. Chem. Soc., 1971)

(untitled) - Smith, E. C.; Metzler, D. E. (J. Am. Chem. Soc., 1963)

(untitled) - McBride, M. M.; Metzler, D. E. (Photochem. Photobiol., 1967)

(untitled) - Heelis, P. F.; Phillips, G. O.; Ahmad, I.; Rapson, H. D. C. (Photobiochem. Photobiophys., 1980)

Flavins Photochemistry and Photobiology - Ahmad, I.; Vaid, F. H. M. (Photochemistry of flavins in aqueous and organic solvents, 2006)

(untitled) - Song, P.-S.; Smith, E. C.; Metzler, D. E. (J. Am. Chem. Soc., 1965)

(untitled) - Treadwell, G. E.; Cairns, W. L.; Metzler, D. E. (J. Chromatogr., 1968)

(untitled) - Schuman Jorns, M.; Schöllnhammer, G.; Hemmerich, P. (Eur. J. Biochem., 1975)

(untitled) - Ahmad, I.; Rapson, H. D. C.; Heelis, P. F.; Phillips, G. O. (J. Org. Chem., 1980)

(untitled) - Ahmad, I.; Fasihullah, Q.; Vaid, F. H. M. (J. Photochem. Photobiol., B: Biol., 2004)

(untitled) - Ahmad, I.; Fasihullah, Q.; Noor, A.; Ansari, I. A.; Ali, Q. N. M. (Int. J. Pharm., 2004)

(untitled) - Ahmad, I.; Fasihullah, Q.; Vaid, F. H. M. (J. Photochem. Photobiol., B: Biol., 2005)

(untitled) - Ahmad, I.; Fasihullah, Q.; Vaid, F. H. M. (J. Photochem. Photobiol., B: Biol., 2006)

(untitled) - Ahmad, I.; Fasihullah, Q.; Vaid, F. H. M. (Photochem. Photobiol. Sci., 2006)

(untitled) - Ahmad, I.; Ahmed, S.; Sheraz, M. A.; Vaid, F. H. M. (J. Photochem. Photobiol., B: Biol., 2008)

(untitled) - Ahmad, I.; Ahmed, S.; Sheraz, M. A.; Aminuddin, M.; Vaid, F. H. M. (Chem. Pharm. Bull., 2009)

(untitled) - Ahmad, I.; Ahmed, S.; Sheraz, M. A.; Vaid, F. H. M.; Ansari, I. A. (Int. J. Pharm., 2010)

(untitled) - Ahmad, I.; Sheraz, M. A.; Ahmed, S.; Kazi, S. H.; Mirza, T.; Aminuddin, M. (Results Pharma Sci., 2011)

(untitled) - Ahmad, I.; Mirza, T.; Iqbal, K.; Ahmed, S.; Sheraz, M. A.; Vaid, F. H. M. (Aust. J. Chem., 2013)

(untitled) - Ahmad, I.; Qadeer, K.; Iqbal, K.; Ahmed, S.; Sheraz, M. A.; Ali, S. A.; Mirza, T.; Hafeez, A. (AAPS PharmSciTech, 2013)

(untitled) - Ahmad, I.; Rapson, H. D. C. (J. Pharm. Biomed. Anal., 1990)

(untitled) - Sheraz, M. A.; Kazi, S. H.; Ahmed, S.; Mirza, T.; Ahmad, I.; Evstigneev, M. P. (J. Photochem. Photobiol., A: Chem., 2014)

(untitled) - Huang, R.; Kim, H. J.; Min, D. B. (J. Agric. Food Chem., 2006)

(untitled) - Oster, G.; Bellin, J. S.; Holmström, B. (Experientia, 1962)

(untitled) - Holmstrom, B. (Ark. Kemi, 1964)

(untitled) - Penzer, G. R. (Biochem. J., 1970)

(untitled) - Penzer, G. R.; Radda, G. K. (Q. Rev., Chem. Soc., 1967)

(untitled) - Penzer, G. R.; Radda, G. K. (Methods Enzymol., 1971)

Flavins and Flavoprotein - Song, P. S. (Chemistry of flavins in their excited states, 1971)

(untitled) - Hemmerich, P. (Fortschr. Chem. Org. Naturst., 1976)

(untitled) - Walsh, C. (Acc. Chem. Res., 1980)

(untitled) - Muller, F. (Photochem. Photobiol., 1981)

(untitled) - Heelis, P. F. (Chem. Soc. Rev., 1982)

Chemistry and Biochemistry of Flavoenzymes - Heelis, P. F. (The photochemistry of flavins, 1991)

(untitled) - Tollin, G. (J. Bioenerg. Biomembr., 1995)

(untitled) - Ahmad, I.; Vaid, F. H. M.; Ahmed, S.; Sheraz, M. A.; Hasan, S. (Int. J. Chem. Anal. Sci., 2010)

(untitled) - Ahmad, I.; Tollin, G. (Biochemistry, 1981)

(untitled) - Ahmad, I.; Tollin, G. (Photochem. Photobiol., 1981)

(untitled) - Vaish, S. P.; Tollin, G. (J. Bioenerg., 1970)

(untitled) - Lasser, N.; Feitelson, J. (Photochem. Photobiol., 1975)

(untitled) - Traber, R.; Vogelmann, E.; Schreiner, S.; Werner, T.; Kramer, H. E. A. (Photochem. Photobiol., 1981)

(untitled) - Traber, R.; Kramer, H. E. A.; Knappe, W. R.; Hemmerich, P. (Photochem. Photobiol., 1981)

(untitled) - Traber, R.; Kramer, H. E. A.; Hemmerich, P. (Pure Appl. Chem., 1982)

(untitled) - Huang, R.; Choe, E.; Min, D. B. (J. Food Sci., 2004)

(untitled) - Choe, E.; Huang, R.; Min, D. B. (J. Food Sci., 2005)

(untitled) - Jung, M. Y.; Oh, Y. S.; Kim, D. K.; Kim, H. J.; Min, D. B. (J. Agric. Food Chem., 2007)

(untitled) - Wahl, P.; Auchet, J. C.; Visser, A. J. W. G.; Müller, F. (FEBS Lett., 1974)

(untitled) - Naman, S. A.; Tegnér, L. (Photochem. Photobiol., 1986)

Effect of complexing agents on photodegradation of riboflavin in aqueous solution - Ahmed, S. (Baqai Medical University, 2009)

(untitled) - Wishner, L. A. (J. Dairy Sci., 1964)

(untitled) - Huang, R.; Choe, E.; Min, D. B. (J. Food Sci., 2004)

Vitamins in Animal and Human Nutrition - McDowell, L. R. (Riboflavin, 2000)

Study of the degradation of riboflavin and related compounds - Ahmad, I. A. (University of London, 1968)

Photolysis of flavins in aqueous and organic solvents - Fasihullah, Q. (University of Karachi, 1988)

(untitled) - Sato, Y.; Yokoo, M.; Takahashi, S.; Takahashi, T. (Chem. Pharm. Bull., 1982)

(untitled) - Mattivi, F.; Monetti, A.; Vrhovšek, U.; Tonon, D.; Andrés-Lacueva, C. (J. Chromatogr., A, 2000)

(untitled) - Becker, E. M.; Cardoso, D. R.; Skibsted, L. H. (Eur. Food Res. Technol., 2005)

(untitled) - Dias, D. A.; Smith, T. A.; Ghiggino, K. P.; Scollary, G. R. (Food Chem., 2012)

(untitled) - Sattar, A.; deMan, J. M.; Alexender, J. C. (Can. Inst. Food Sci. Technol. J., 1977)

(untitled) - Sue-Chu, M.; Kristensen, S.; Tonnesen, H. H. (Pharmazie, 2009)

Photostability of drugs and drug formulation - Moore, D. E. (Standardization of kinetic studies of photodegradation reactions, 2004)

(untitled) - Ina, S. (Tohoku Med. J., 1959)

(untitled) - Guttman, D. E. (J. Pharm. Sci., 1962)

(untitled) - Surrey, A. R.; Nachod, F. C. (J. Am. Chem. Soc., 1951)

The Merck Index - O’Neil, M. J. (Royal Society of Chemistry, Merck & Co., Inc., 2013)

(untitled) - Penzkofer, A.; Tyagi, A.; Kiermaier, J. (J. Photochem. Photobiol., A: Chem., 2011)

(untitled) - Song, P.-S.; Metzler, D. E. (Photochem. Photobiol., 1967)

(untitled) - Holmström, B.; Oster, G. (J. Am. Chem. Soc., 1961)

(untitled) - Moore, W. M.; Spence, J. T.; Raymond, F. A.; Colson, S. D. (J. Am. Chem. Soc., 1963)

(untitled) - Moore, W. W.; Ireton, R. C. (Photochem. Photobiol., 1977)

(untitled) - Gutiérrez, I.; Criado, S.; Bertolotti, S.; García, N. A. (J. Photochem. Photobiol., B, 2001)

(untitled) - Insińska-Rak, M.; Golczak, A.; Sikorski, M. (J. Phys. Chem. A, 2012)

(untitled) - Halwer, M. (J. Am. Chem. Soc., 1951)

(untitled) - Asker, A. F.; Habib, M. J. (Drug Dev. Ind. Pharm., 1990)

(untitled) - Ahmad, I.; Anwar, Z.; Iqbal, K.; Ali, S. A.; Mirza, T.; Khurshid, A.; Khurshid, A.; Arsalan, A. (AAPS PharmSciTech, 2014)

Stability of Drugs and Dosage Forms - Yoshioka, S.; Stella, V. J. (Kluwer Academic/Plenum Publishers, 2000)

(untitled) - Silber, J.; Previtali, C.; Silbera, N. (J. Agric. Food Chem., 1976)

(untitled) - Sato, Y.; Chaki, H.; Suzuki, Y. (Chem. Pharm. Bull., 1984)

(untitled) - Wadke, D. A.; Guttman, D. E. (J. Pharm. Sci., 1964)

(untitled) - Wadke, D. A.; Guttman, D. E. (J. Pharm. Sci., 1966)

(untitled) - Wadke, D. A.; Guttman, D. E. (J. Pharm. Sci., 1966)

(untitled) - Dudutz, G.; Ristea, I. (Rev. Med. (Tirgu-Mures, Rom.), 1978)

(untitled) - Koziol, J. (Photochem. Photobiol., 1966)

(untitled) - Koziol, J. (Experientia, 1965)

(untitled) - Koziol, J. (Photochem. Photobiol., 1966)

(untitled) - Koziol, J.; Knobloch, E. (Biochim. Biophys. Acta, 1965)

(untitled) - Ahmad, I.; Fasihullah, Q. (Pak. J. Pharm. Sci., 1990)

(untitled) - Ahmad, I.; Fasihullah, Q. (Pak. J. Pharm. Sci., 1991)

(untitled) - Roy, D. K.; Saha, A.; Mukherjee, A. K. (Spectrochim. Acta, Part A, 2006)

(untitled) - Filipowicz, A.; Wołowiec, S. (Int. J. Pharm., 2011)

(untitled) - Ahmad, I.; Sheraz, M. A.; Ahmed, S.; Shaikh, R. H.; Vaid, F. H. M.; Khattak, S. U. R.; Ansari, S. A. (AAPS PharmSciTech, 2011)

(untitled) - Ahmad, I.; Bano, R.; Sheraz, M. A.; Ahmed, S.; Mirza, T.; Ansari, S. A. (Acta Pharm., 2013)

(untitled) - Wilson, J. E. (Biochemistry, 1966)

(untitled) - DeRitter, E. (J. Pharm. Sci., 1982)

(untitled) - Guttman, D. E.; Athalye, M. Y. (J. Am. Pharm. Assoc., Sci. Ed., 1960)

(untitled) - Tsibris, J. C. M.; McCormick, D. B.; Wright, L. D. (Biochemistry, 1965)

(untitled) - Evstigneev, M. P.; Rozvadovskaya, A. O.; Hernandez Santiago, A. A.; Mukhina, Y. V.; Veselkov, K. A.; Rogova, O. V.; Davies, D. B.; Veselkov, A. (Russ. J. Phys. Chem., 2005)

(untitled) - Loukas, Y. L. (J. Pharm. Biomed. Anal., 2001)

(untitled) - Wang, X.-M.; Chen, H.-Y. (Spectrochim. Acta, Part A, 1996)

(untitled) - Loukas, Y. L.; Vraka, V.; Gregoriadis, G. (J. Pharm. Pharmacol., 1997)

(untitled) - Wang, X.-m.; Yan, M.-d.; Zhu, J.-j.; Chen, H.-Y. (J. Electroanal. Chem., 1998)

(untitled) - Terekhova, I. V.; Koźbiał, M.; Kumeev, R. S.; Alper, G. A. (J. Solution Chem., 2011)

(untitled) - Terekhova, I. V.; Tikhova, M. N.; Volkova, T. V.; Kumeev, R. S.; Perlovich, G. L. (J. Inclusion Phenom. Macrocyclic Chem., 2011)

(untitled) - de Jesus, M. B.; Fraceto, L. F.; Martini, M. F.; Pickholz, M.; Ferreira, C. V.; de Paula, E. (J. Pharm. Pharmacol., 2012)

(untitled) - Lilletvedt, M.; Kristensen, S.; Tønnesen, H. H. (Pharmazie, 2010)

(untitled) - Thomas, T. P.; Choi, S. K.; Li, M.-H.; Kotlyar, A.; Baker, J. R., Jr (Bioorg. Med. Chem. Lett., 2010)

(untitled) - Ramu, A.; Mehta, M. M.; Liu, J.; Turyan, I.; Aleksic, A. (Cancer Chemother. Pharmacol., 2000)

(untitled) - Massad, W. A.; Barbieri, Y.; Romero, M.; García, N. A. (Photochem. Photobiol., 2008)

(untitled) - Ishizaka, S.; Nishijima, Y.; Kitamura, N. (Anal. Bioanal. Chem., 2006)

(untitled) - Miskoski, S.; Garcia, N. A. (Collect. Czech. Chem. Commun., 1991)

(untitled) - Martinez, G.; Zimerman, O. E.; Garcia, N. A. (Collect. Czech. Chem. Commun., 1993)

(untitled) - Frouin, A.; Bazile, J.; Jondeau, D. (Ann. Nutr. Aliment., 1978)

(untitled) - Benecky, M.; Yu, T.-J.; Watters, K. L.; McFarland, J. T. (Biochim. Biophys. Acta, 1980)

(untitled) - Ahmad, I.; Sheraz, M. A.; Ahmed, S.; Bano, R.; Vaid, F. H. M. (Int. J. Cosmet. Sci., 2012)

(untitled) - Cardoso, D. R.; Olsen, K.; Skibsted, L. H. (J. Agric. Food Chem., 2007)

(untitled) - Baldursdóttir, S. G.; Kjøniksen, A.-L.; Karlsen, J.; Nyström, B.; Roots, J.; Tønnesen, H. H. (Biomacromolecules, 2003)

(untitled) - Cardoso, D. R.; Homem-de-Mello, P.; Olsen, K.; da Silva, A. B. F.; Franco, D. W.; Skibsted, L. H. (J. Agric. Food Chem., 2005)

(untitled) - Natera, J.; Massad, W.; García, N. A. (Photochem. Photobiol. Sci., 2012)

(untitled) - Hiraku, Y.; Ito, K.; Hirakawa, K.; Kawanishi, S. (Photochem. Photobiol., 2007)

(untitled) - Bradley, D. G.; Kim, H. J.; Min, D. B. (J. Agric. Food Chem., 2006)

(untitled) - Sue-Chu, M.; Kristensen, S.; Tønnesen, H. H. (Pharmazie, 2008)

(untitled) - Chen, S.; Guzei, I. A.; Yu, L. (J. Am. Chem. Soc., 2005)

(untitled) - Tonnesen, H. H.; Brunsvik, A.; Loseth, K.; Bergh, K.; Gederaas, O. A. (Pharmazie, 2007)

(untitled) - Loukas, Y. L. (Analyst, 1997)

(untitled) - Habib, M. J.; Asker, A. F. (J. Parenter. Sci. Technol., 1991)

(untitled) - Chauhan, S. M.; Awasthi, A. (Indian J. Biochem. Biophys., 1995)

(untitled) - Arien, A.; Dupuy, B. (J. Microencapsulation, 1997)

(untitled) - Bhowmik, B. B.; Sil, A. (Chem. Phys. Lipids, 2004)

(untitled) - Sen-Varma, C.; Ghosh, S.; Bhowmik, B. B. (Chem. Phys. Lipids, 1995)

(untitled) - Ionita, M. A.; Ion, R. M.; Cârstocea, B. (Oftalmologia, 2003)

(untitled) - Bekbolet, M. (J. Food Prot., 1990)

(untitled) - Mestdagh, F.; De Meulenaer, B.; De Clippeleer, J.; Devlieghere, F.; Huyghebaert, A. (J. Dairy Sci., 2005)

(untitled) - Webster, J. B.; Duncan, S. E.; Marcy, J. E.; O'Keefe, S. F. (J. Food Sci., 2009)

(untitled) - Intawiwat, N.; Pettersen, M. K.; Rukke, E. O.; Meier, M. A.; Vogt, G.; Dahl, A. V.; Skaret, J.; Keller, D.; Wold, J. P. (J. Dairy Sci., 2010)

(untitled) - Marsh, R.; Kajda, P.; Ryley, J. (Nahrung, 1994)

United States Pharmacopeia 30 / National Formulary 25 (United States Pharmacopeial Convention, Inc., 2007)

(untitled) - Farrer, K. T. H.; MacEwan, J. L. (Aust. J. Biol. Sci., 1954)

(untitled) - Masłowska, J.; Malicka, M. (J. Therm. Anal., 1988)

(untitled) - Loy, H. W., Jr; Haggerty, J. F.; Combs, E. L. (Food Res., 1951)

(untitled) - Ahmad, I.; Beg, A. E.; Zoha, S. M. S. (Karachi Univ. J. Sci., 1972)

(untitled) - Ahmad, I.; Beg, A. E.; Zoha, S. M. S. (Karachi Univ. J. Sci., 1973)

Clarke’s Analysis of Drugs and Poisons - Moffat, A. C.; Osselton, M. D.; Widdop, B. (Pharmaceutical Press, 2011)

Dairy Chemistry and Biochemistry - Fox, P. F.; McSweeney, P. L. H. (Thomson Science, 1998)

(untitled) - Nisha, P.; Singhal, R. S.; Pandit, A. B. (Food Chem., 2005)

(untitled) - Kajihausa, O. E.; Sobukola, O. P.; Idowu, M. A.; Awonorin, S. O. (Int. Food Res. J., 2010)

(untitled) - Kwok, K.-C.; Shiu, Y.-W.; Yeung, C.-H.; Niranjan, K. (J. Sci. Food Agric., 1998)

(untitled) - Shuguang, Z.; Xiancheng, Z.; Linli, L.; Chengrong, L.; Tao, L.; Tao, Y.; Ning, H. W. (Chin. J. Pharm. Sci., 2002)

(untitled) - Masłowska, J.; Malicka, M. (J. Therm. Anal., 1987)

(untitled) - Astanov, S.; Sharipov, M. Z.; Fayzullaev, A. R.; Kurtaliev, E. N.; Nizomov, N. (J. Mol. Struct., 2014)

(untitled) - Ahmad, I.; Vaid, F. H. M. (J. Chem. Soc. Pak., 2008)

(untitled) - Guttman, D. E.; Platek, T. E. (J. Pharm. Sci., 1967)